Handbook of administrative ethics - Cooper, Terry L., 1938- (Public administration and public policy, 2001)
This handbook follows the discussion of ethics in significant pieces of public administration literature from the late-19th century to the start of the 21st. It offers theoretical perspective, illustrative cases, and empirical research. This edition includes a new chapter on military ethics.